2015
DOI: 10.1136/gutjnl-2015-310327
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Siglec-7 expression identifies a dysfunctional natural killer cell subset associated with liver inflammation and fibrosis in chronic HCV infection

Abstract: These findings identify Siglec-7 NK cells as a dysfunctional subpopulation associated with severe liver disease in chronic HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 38 publications
(37 reference statements)
3
45
0
Order By: Relevance
“…In Figure 2, we show similar correlation coefficients between Siglec-7 and these serologies as Varchetta et al did, highlighting the reproducibility of the Siglec-7 assay in a distinct population. (14) We are able to build on these findings in our prospective study by extending that serum Siglec-7 levels were associated with increased mortality in an independent cohort. This helps confirm an important connection between liver inflammation, immune dysregulation, and clinical outcomes in cirrhosis.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In Figure 2, we show similar correlation coefficients between Siglec-7 and these serologies as Varchetta et al did, highlighting the reproducibility of the Siglec-7 assay in a distinct population. (14) We are able to build on these findings in our prospective study by extending that serum Siglec-7 levels were associated with increased mortality in an independent cohort. This helps confirm an important connection between liver inflammation, immune dysregulation, and clinical outcomes in cirrhosis.…”
Section: Discussionmentioning
confidence: 67%
“…highlighted the potential pathobiologic connection between Siglec-7, immune dysregulation, and severe liver disease. (14) In a large cross-sectional study, these investigators demonstrated an increase in soluble serum Siglec-7 in a population with hepatitis C infection, and a correlation between Siglec-7 and levels of other clinical biomarkers of liver disease. This suggests that higher soluble Siglec-7 may denote a high inflammatory state in the liver and may be mechanistically important in this disease process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among circulating immune cells constitutively expressing this C-lectin-type molecule (i.e., NK cells and monocytes) (5), the main source of sSiglec-7 seems to be NK cells because a subset of Siglec-7 neg monocytes has never been reported during the course of HIV-1 infection (52). Similarly, it has been recently shown that also the stimulation in vitro of NK cells with HCV induces both a significant release of sSiglec-7 in culture supernatant and a decrease of Siglec-7 expression from NK cell surface (77). Further investigations are required to identify the cellular and molecular mechanisms that certain viruses employ to induce a shedding of this C lectin-type receptor selectively on NK cells during the acute phases of the infection.…”
Section: Kinetics Of Siglecs During the Course Of Hiv-1 Infectionmentioning
confidence: 97%